eCM 2017
DOI: 10.22203/ecm.v034a09
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte expansion is associated with loss of primary cilia and disrupted hedgehog signalling

Abstract: Tissue engineering-based therapies targeting cartilage diseases, such as osteoarthritis, require in vitro expansion of articular chondrocytes. A major obstacle for these therapies is the dedifferentiation and loss of phenotype accompanying chondrocyte expansion. Recent studies suggest that manipulation of hedgehog signalling may be used to promote chondrocyte re-differentiation. Hedgehog signalling requires the primary cilium, a microtubule-based signalling compartment, the integrity of which is linked to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 58 publications
2
41
0
Order By: Relevance
“…The IFT88 ORPK mutation, which results in changes to matrix patterning in cartilage in vivo (33), renders cells unable to express fulllength IFT88 and assemble a primary cilium. This has also previously been associated with the regulation of multiple chondrocyte responses (37)(38)(39)(47)(48)(49), most of which are proposed to be indicative of roles for the cilium. Importantly, however, IFT88, and indeed this mutation, are both associated with cell biology that is not proven to be attributable to cilia function-for example, migration (50), cell division (51), and planar cell polarity (52).…”
Section: Discussionmentioning
confidence: 73%
“…The IFT88 ORPK mutation, which results in changes to matrix patterning in cartilage in vivo (33), renders cells unable to express fulllength IFT88 and assemble a primary cilium. This has also previously been associated with the regulation of multiple chondrocyte responses (37)(38)(39)(47)(48)(49), most of which are proposed to be indicative of roles for the cilium. Importantly, however, IFT88, and indeed this mutation, are both associated with cell biology that is not proven to be attributable to cilia function-for example, migration (50), cell division (51), and planar cell polarity (52).…”
Section: Discussionmentioning
confidence: 73%
“…Elongation of osteocyte primary cilia using fenoldopam or lithium has been shown to be associated with increased ciliary mechanosensitivity 37 . In chondrocytes, mechanically-induced cilia disassembly inhibits hedgehog signalling 29 , 38 . Previous studies have also shown that cilia set length regulates injection of intraflagellar transport (IFT) cargoes as part of the balance point model first proposed by Marshall 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Actin depolymerization induced by cytochalasin D in chondroprogenitor cells resulted in cytoplasmic localization of YAP/TAZ and downregulation of collagen type I gene expression (Zhong et al, ). There is evidence suggesting that actin polymerization status may affect a plethora of cellular processes (Carpenter, ) and cellular structures such as primary cilia, which may influence levels of transforming growth factor, Wnt, hedgehog, and mechanosignalling (Thompson et al, ). These factors have been shown to affect chondrocyte proliferation and differentiation to influence cartilage growth and metabolism.…”
Section: Discussionmentioning
confidence: 99%